Konsumsi Jus Buah Bit dan Lemon untuk Meningkatkan Kadar Hemoglobin pada Ibu Hamil - Cholisah Suralaga; Irma Kurniyawati (FORIKES, 2022)
Anemia is a factor in maternal mortality, where the incidence of anemia in 2019 in Tangerang Regency is 63%. The purpose of this study was to determine the effect of consumption of beetroot and lemon juice on hemoglobin levels in pregnant women. The design of this research is pretest-posttest with control group. The samples of this study were 15 pregnant women as the experimental group and 15 pregnant women as the control group which were selected by purposive sampling technique. The collected data were analyzed using independent sample t-test. The results of the descriptive analysis showed that the average increase in Hb levels in the experimental group = 0.946 and the control group = 0.380. The results of the comparative analysis showed the value of p = 0.000. It was concluded that there was an effect of consumption of beetroot and lemon juice on hemoglobin levels in pregnant women.Keywords: anemia; pregnant mother; beet juice; lemon juice ABSTRAK Anemia merupakan salah satu faktor kematian ibu, di mana angka kejadian anemia pada tahun 2019 di Kabupaten Tangerang yaitu 63%. Tujuan penelitian ini adalah untuk mengetahui pengaruh konsumsi jus buah bit dan lemon terhadap kadar hemoglobin pada ibu hamil. Rancangan penelitian ini adalah pretest-posttest with control group. Sampel penelitian ini adalah 15 ibu hamil sebagai kelompok eksperimen dan 15 ibu hamil sebagai kelompok kontrol yang dipilih dengan teknik purposive sampling. Data yang telah terkumpul dianalisis menggunakan independent sample t-test. Hasil analisis deskriptif menunjukkan bahwa rerata peningkatan kadar Hb pada kelompok ekperimen = 0,946 dan kelompok kontrol = 0,380. Hasil analisis perbandingan menunjukkan nilai p = 0,000. Disimpulkan bahwa ada pengaruh konsumsi jus buah bit dan lemon terhadap kadar hemoglobin pada ibu hamil. Kata kunci: anemia; ibu hamil; jus buah bit; jus lemon